Implementation of Stakeholder Engagement at PT Sentra Textil - Fitra Ruliyana Salimudin; Jesika Putri Thion; Adrian Pilua (Universitas 17 Agustus 1945 Semarang, 2023)
The Textile sector is intimately associated with business continuity difficulties because of the impact of its operational activities. since a result, sustainability reports are crucial for textile companies since they provide a means of satisfying stakeholders' requirements and expectations. PT Sentra Textil, a gas company, hasn't released a stand-alone sustainability report or registered with Proper yet. Thus, the purpose of this research, as a single case study, is to examine PT Sentra Textil's stakeholder engagement design and identify relevant subjects that will serve as the foundation for the company's sustainability report. Data collection methods included documentary studies and interviews. More information about stakeholder involvement and its connection to important subjects is provided by this study. The study's findings are anticipated to help PT Sentra Textil management successfully manage stakeholder interaction, pinpoint the most crucial concerns, and create an independent sustainability report that satisfies the requirements and expectations of all PT Sentra Textil stakeholders. Because it hasn't been applied at every stage, the monitoring stage—one of the four stages of stakeholder engagement design—is still not carried out successfully. Aside from that, PT Sentra Textil has 14 material topics. Four of those themes are the most crucial since they affect PT Sentra Textil stakeholders the most.